The Doomsday Scenario Depicted by Frau Ava: The Question of Sources - Burov, Aleksej (Respectus Philologicus, 2020)
The present article explores an excerpt depicting the scenario of the last days in the poem Das Jüngste Gericht (Eng. The Last Judgement), written by the first-named German female writer Frau Ava (circa 1060–1127). The study addresses the question of sources used in the depiction of the end times in the excerpt under consideration (lines 1–160). The study does not question the affinity between the scenes of the last days illustrated in the excerpt and the apocalyptic plot of the Latin texts of Pseudo-Beda (the turn of the 12th century) and Petrus Daminanus (1006–1072); however, it is assumed that Frau Ava may have drawn not only on the aforementioned Latin sources but also on the apocalyptic song Muspilli, written by an anonymous author circa 870. The analysis of the excerpt suggests that the apocalyptic narrative of Muspilli may have shaped the scene of the fifteenth day illustrated in the poem The Last Judgement. Moreover, Frau Ava, unlike Pseudo-Beda and Petrus Daminanus, does not refer to St. Jerome as a source of information but to wisten (Eng. wise men). As no evidence of other German apocalyptic texts referring to wise men, except for Muspilli, can be found, the study concludes that depicting the scenario of the last days in her poem, in addition to the Latin texts, Frau Ava used the song Muspilli as her source.
Keywords: Frau Ava; The Last Judgement; sources